A systematic review of as needed versus treat and extend ranibizumab or bevacizumab treatment regimens for neovascular age-related macular degeneration. Issue 7 (29th October 2015) - Chin-Yee, David; Eck, Thomas; Fowler, Susan; Hardi, Angela; Apte, Rajendra S
Abstract : Purpose: To evaluate the relative efficacy of as needed versus treat and extend regimen for the treatment of neovascular age-related macular degeneration (AMD). Methods: We conducted a systematic review of studies that evaluated the efficacy of as needed or treat and extend regimen for neovascular AMD by searching multiple databases up to December 2013. Included studies were selected based on study duration of no less than 12 months, availability of outcome data, treatment protocol for as needed groups or pro re nata (PRN) receiving bevacizumab or ranibizumab, and all studies with treat extend protocols following the 'inject and extend' regimen. The outcome data were pooled and analysed. Results: 1046 peer reviewed articles meeting our initial search criteria were returned. After further review by two independent reviewers, 8 studies meeting treat and extend protocol and 62 studies meeting PRN protocol were included. The mean improvement in visual acuity in the PRN group was 5.4 ETDRS letters compared with 10.4 ETDRS letters in the treat and extend group. The PRN group received an average of 5.60 injections at 1 year compared with 8.09 in the treat and extend group. Central retinal thickness improved on average by 100.32 µ in the PRN group compared with 87.7 µ in the treat and extend group. Conclusions: Though our study suggests superiority of the treat and extend regimen to PRN treatment in a 12-month period, this review demonstrates the need for randomised clinical trials to confirm our findings and to evaluate long-term efficacy outcomes with these regimens compared with monthly therapy.